1954
DOI: 10.1002/jsfa.2740050706
|View full text |Cite
|
Sign up to set email alerts
|

Studies on egg shells. IV.—The site of deposition of radioactive calcium and phosphorus

Abstract: Egg shells from birds fed with either radioactive calcium or phosphorus have been examined by taking autoradiographs of tangential sections. The autoradiographs for calcium show a distinctive form of layering, which can be correlated with time of laying. This is interpreted as indicating that the supply of calcium to the shell gland may be made up entirely of food calcium or entirely of bone calcium or of varying proportions of the two, depending upon the time of day that a particular layer of the shell was be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1956
1956
2010
2010

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…If the digestive system contains decreased levels of calcium, the skeletal system becomes a very important source of calcium for the forming shell. Tyler (1954) assumed from several studies that there was a period in the early morning hours when absorption of dietary calcium from the previous day's food ends and calcium for egg shell formation is supplied largely from the skeleton. Histological studies of medullary bone by Bloom et al (1958) and Stringer (1962) confirmed Tyler's assumption.…”
Section: Introductionmentioning
confidence: 99%
“…If the digestive system contains decreased levels of calcium, the skeletal system becomes a very important source of calcium for the forming shell. Tyler (1954) assumed from several studies that there was a period in the early morning hours when absorption of dietary calcium from the previous day's food ends and calcium for egg shell formation is supplied largely from the skeleton. Histological studies of medullary bone by Bloom et al (1958) and Stringer (1962) confirmed Tyler's assumption.…”
Section: Introductionmentioning
confidence: 99%
“…The reason for this is unknown. Tyler (1954) concluded that there was a period in the early hours of the morning between the time when absorption of di-etary calcium from the previous day's food ends and absorption from the current day's food begins when calcium for shell formation comes largely from the skeleton. This conclusion was later supported by the results of histological studies of the medullary bone of laying hens at different stages of egg shell calcification (Bloom et al, 1958;and Stringer, 1962).…”
Section: Discussionmentioning
confidence: 97%
“…Hertelendy, 1961), no information is available on the dynamic equilbria between absorbed dietary Ca, skeletal Ca and the blood Ca pool from which material for the shell is drawn. From observations on the shell, following the feeding of 45Ca, Tyler (1954) has concluded that the supply of Ca to the shell gland may be made up entirely of Ca from the food, or from the bone, or from varying proportions, depending upon the time of day. T o study these relationships and to determine the quantitative contribution of diet and skeleton, a double radioisotope labelling technique was used with Shaver Starcross 288 hens fed on a diet containing 3 % Ca.…”
Section: The Interrelationship Between Food and Water Intake And Egg mentioning
confidence: 99%